A case report of a child with sepsis induced multiorgan failure and massive complement consumption treated with a short course of Eculizumab: A case of crosstalk between coagulation and complement?. Issue 4 (January 2019) - Galic, Slobodan; Csuka, Dorottya; Prohászka, Zoltán; Turudic, Daniel; Dzepina, Petra; Milosevic, Danko
Abstract: Rationale: This article describes a child with a life-threatening multiorgan failure with disseminated intravascular coagulation (DIC) and massive complement consumption. To our knowledge this therapeutic approach was for the first time effectively applied in a pediatric patient. Patient concerns: A 14-month-old boy was presented with a severe, rapidly progressing, life-threatening disease because of sudden onset of fever, hemathemesis, hematuria, and bloody diarrhoea alongside fast spreading hematomas and general corporeal edema. Diagnosis: The most plausible diagnosis in our patient is Clostridium difficile sepsis-induced thrombotic microangiopathy alongside with DIC and consumption coagulopathy. The diagnosis was confirmed by positive C difficile bacteria strain in coproculture, clinical, and laboratory tests affirming DIC and global complement activation and consumption. Interventions: The patient was treated with antibiotics (Metronidazole, Vancomycin), plasmapheresis, dialysis, methylprednisolone, mycophenolate mofetil, and Eculizumab. Outcomes: The child is in fair overall condition in a 2 year follow-up with no complications save chronic renal failure. Lessons: In rare cases of sepsis with massive complement consumption, a case-sensitive Eculizumab therapy may be at least considered after the resolution of life-threatening multiorgan failure. The application of this drug can be performed only after sepsis induced disease is put under control. A fast withdrawal of Eculizumab after control of massive complement consumption is recommended to prevent triggering of second sepsis reactivation.